The happiness of being a doctor - Paico-Vílchez, Emiliano (2023)
In this article, the author makes a study of some biblical reviews that imprint a divine character on the mission or work of the physician. Therefore, he considers that practicing medicine is a reason for happiness, a spiritual rejoicing that motivates to follow the example of Jesus Christ and the Good Samaritan, and to exercise the beautiful and noble profession with vigilant and solicitous presence at the side of the sick.